Micro - organisms in foods 5 : (Blackie academic and Professional, 1996)
The control of food safety in modern food processing relies upon HACCP and other systems that identify hazards and define processes to control them. These demand a thorough understanding of the properties of microbial pathogens under all the conditions that could be found in foods and the food processing environment. Detailed information about each of the main organisms responsible for causing microbial food poisoning is presented here in an accessible and systematic way. An overview of key properties for each organism is followed by a series of tables detailing the response of the organism under a range of variable conditions. This information has been prepared by the International Commission for the Microbiological Specifications of Foods (ICMSF).